Die Herrschaft des politischen Islam als eine Form des Totalitarismus »Die Islamische Republik Iran« - Wahdathagh, Wahied (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
The Revolution of 1979 in Iran ended in a new form of dictatorship. The discussion on an Islamic Civil Society in Iran irritates, because the modell of Jameeje-Madani is the archaic caliphate and not a modern pluralistic and democratic State. Nevertheless from a technological point of view Iran is a part of the modern world. This fact causes the third form of a totalitarian form of dictatorship. The economical support, in the name of liberalization, stabilizes the totalitarian reign of the caste of the clergymen.